Language in the schools : integrating linguistic knowledge into K-12 teaching - Denham, Kristin E., 1967-; Lobeck, Anne C. (L. Erlbaum Associates, 2005)
This book asks: What aspects of linguistic knowledge are most useful for teachers to know? What kinds of activities and projects are most effective in introducing those aspects of linguistic knowledge to K-12 students? The volume focuses on how basic linguistic knowledge can inform teachers' approaches to language issues.